2018
DOI: 10.2215/cjn.01390118
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Treatment with Corticosteroids and Recovery of Kidney Function in Acute Interstitial Nephritis

Abstract: Background and objectives Drug-induced acute interstitial nephritis represents an emerging cause of acute kidney disease, especially among polymedicated elderly patients. Although corticosteroids are frequently used, controversy exists about the timing of initiation, efficacy, safety, and duration of treatment.Design, setting, participants, & measurements We performed a retrospective study of 182 patients with biopsy-proven drug-induced acute interstitial nephritis from 13 Spanish centers. Exposure was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 19 publications
4
81
0
4
Order By: Relevance
“…Tubular atrophy and interstitial fibrosis [which is highly correlated to TA ( R = 0.98)] are markers of chronic tubulointerstitial damage with recognised prognostic implications in a diverse range of conditions . Increasing severity of TA and interstitial fibrosis have been shown to be associated with poor renal outcomes in AIN . Our finding that TA score is a predictor of poor renal recovery is consistent with these studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Tubular atrophy and interstitial fibrosis [which is highly correlated to TA ( R = 0.98)] are markers of chronic tubulointerstitial damage with recognised prognostic implications in a diverse range of conditions . Increasing severity of TA and interstitial fibrosis have been shown to be associated with poor renal outcomes in AIN . Our finding that TA score is a predictor of poor renal recovery is consistent with these studies.…”
Section: Discussionsupporting
confidence: 88%
“…More recent studies have largely focused on the potential influence of corticosteroid treatment in the management of AIN . However, Muriithi et al found that increased tubular atrophy (TA) correlated with a poor response to corticosteroids while, in a multicentre retrospective study of steroid‐treated AIN, the presence of >50% interstitial fibrosis was associated with a reduced likelihood of renal recovery …”
Section: Introductionmentioning
confidence: 99%
“…If we do try to apply the lessons learned from druginduced AIN to the management of ICI-related AIN, then understanding the role of steroids is also important. Early steroid initiation in addition to drug withholding is recommended because delays are associated with poorer kidney outcomes (22,23). Therefore, we should strongly consider kidney biopsy when in doubt because delaying diagnosis may affect kidney recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Few clinical trials are available to guide this aspect of AIN care: observational studies, case series, and case reports define the field. Although the literature is somewhat inconsistent, it does appear that corticosteroids favorably affect renal recovery in drug-associated AIN (5,6,11,12).…”
Section: Managementmentioning
confidence: 99%